Optimal UAV coordination for target tracking using dynamic programming - Quintero, S.; Papi, Francesco; Klein, D.; Chisci, L.; Hespanha, J. (2010)
This work focuses on optimal routing for two camera-equipped UAVs cooperatively tracking a single target moving on the ground. The UAVs are small fixed-wing aircraft cruising at a constant speed and fixed altitude; consequently, the vehicles are modeled as planar Dubins vehicles. A perspective transformation, relating the image-plane measurements to the ground, allows derivation of the geolocation (target localization) error covariance. Using dynamic programming, we compute optimal coordinated control policies which minimize the fused geolocation error covariance. A surprising result, and the main contribution of this work, is that the dominant factor governing the optimal UAV routes is coordination of the distances to the target, not of the viewing directions as is traditionally assumed. ©2010 IEEE.